EARLY CEREBRAL REVASCULARIZATION FOR THE PREVENTION OF RECURRENT ISCHEMIC STROKE - Kilichev Farrukh Akhmadovich (Research Focus International Scientific Journal, 2025)
This study aimed to evaluate the safety and efficacy of early surgical revascularization of the brachiocephalic arteries in patients with acute ischemic stroke. Seven patients underwent carotid endarterectomy or stenting within 7 days of symptom onset. Surgical intervention was performed after stabilization of neurological status at a low NIHSS score. Clinical outcomes, complication rates, and neurological improvement were analyzed and compared with international literature. The results suggest that, with strict patient selection (neurological deficit ≤3 on Rankin and lesion size ≤4 cm), early revascularization may be both safe and associated with improved neurological recovery. Current global data support this strategy for both endarterectomy and stenting. However, broader studies are needed to confirm these findings and develop standardized inclusion criteria.